STRATEGI USAHA MIKRO KECIL DAN MENENGAH (UMKM) DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 DI KABUPATEN PASURUAN - Hermi Sularsih; Akhamad Nasir (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
The purpose of this study is to determine the strategies implemented by micro, small and medium enterprises (MSMEs) to face the era of the industrial revolution 4.0. The method used in this research is a qualitative method with descriptive analysis techniques using data reduction, data presentation and conclusion and SWOT analysis. The informants in this study were food and beverage micro, small and medium enterprises (UMKM) registered at the Office of Cooperatives and Micro Enterprises in Pasuruan Regency. The results of this study are the position of the food and beverage business SMEs in facing the Industrial Revolution Era 4.0 in Pasuruan Regency is in cell V of the IE matrix. Strategies that can be applied include the Strategy Opportunities (SO) strategy by maximizing the strengths owned and paying attention to all market opportunities. This strategy needs to be supported by efforts to increase manpower/human resources with technological capabilities, strategic locations and the availability of relatively cheap raw materials with government support.